Hybrid Contracts Ditinjau dari Perspektif Hadits - Jauhari, Sofuan (Ngabari: Jurnal Studi Islam dan Sosial, 2020)
This study aims to determine how the law of hybrid contracts according to the hadith reviews. The literature study method was used in this research. Researchers found several hadiths about the prohibition of baiataini fi baiatin. After being traced based on their sanad and matan, the quality of these hadiths is shahih or authentic. Islamic economists and Muslim bankers use the hadith about the prohibition of baiataini fi baiatin as a guideline for determining the prohibition of hybrid contracts. Furthermore, the existence of research on the quality of this hadith will be beneficial for people to increase their confidence in rejecting or avoiding transactions categorized as hybrid contracts.